COMPARATIVE ANALYSIS OF MULTIVALUED PHRASEOLOGICAL UNITS OF THE RUSSIAN AND UZBEK - Baratov Rashid Gulamovich (American Journals, 2022)
The article is devoted to the little-studied phenomenon of phraseological polysemy in the Russian and Uzbek languages. Comparative analysis of multivalued correlates revealed a complex picture of the relationship between the meanings of FE in the Russian and Uzbek languages, confirming the hypothesis that two multivalued phraseological units of different languages in rare cases correspond to all their meanings.
Keywords: phraseological unit, phraseological polysemy, contrastive analysis, interlanguage equivalence.